Potential of Philippine sunflower variants for the phytoremediation of copper contaminated substrate - Poral, Neil Phillip J. (Animo Repository, 2020)
Phytoremediation is the process of using plants to remove, degrade, and stabilize contaminants in water and soil. In this study Sunflower (Helianthus annuus) is used for the phytoremediation of copper-contaminated soil since it is fast-growing and can accumulate heavy metals in soil. Three variants of Philippine Sunflower (F1 Vincent 2 Choice, F1 Vincent 2 Fresh, and Sunrich Orange) were evaluated for the phytoremediation of soil with 177.16 ppm Cu as Cu2+ . Among the three variants, F1 Vincent 2 Choice performed the best in terms of Cu uptake at 3574.22 mg Cu/kg dry biomass. It is also noteworthy that with higher Cu concentration and longer exposure time, more Cu is removed from the soil with Cu concentrations ranging 124.84 – 242.16 ppm. It can be observed that H. annuus is a good hyperaccumulator with a bioconcentration factor (BCF) after 3 weeks ranging from 6.7 – 10.2. Also, during the early stages more Cu was found to concentrate within the roots. However, with longer exposure time, Cu was observed to be translocated to the aerial parts, i.e. the shoots. The translocation factor (TF) after 3 weeks ranging from 0.17 – 0.23. The Cu concentration in the roots was always higher than that of the shoots. Interestingly, in the latter stages, the total amount of Cu in the shoots was always higher than that of the roots due to the amount of biomass. The Cu uptake kinetics of H. annuus was evaluated and it was found out that it best fits with an n=0.7 order model with an average R2 value of 0.967 with a rate constant, k, of 0.0475-0.0491 mg0.3 -kg-0.3 -wk-1 .